PENGARUH PRODUK, PROMOSI DAN SIKAPTERHADAP KEPUTUSAN NASABAH DI DALAM MEMILIHJASA PERBANKAN SYARIAH (Studi Kasus Pada BNI Syariah 46 Cab. Kota Semarang) - Singgih Adi Indyarto, 08.05.51.0133; Yulianto, Heru (Students Journal of Economic and Management, 2012)
The purpose of this researches is to investigated the effects of product, promotion and attitude on clientele decision to choose sharia banking service. Data are collected through questionnairemetode of 120 clientele on branch of BNI Sharia in Semarang City, which is obtained by using accidental sampling technique. The analyze data use multiple regression model, from the analysis get result show of this regression equation: Y = - 0,045 X1 + 0,328 X2 + 0,349 X3 Whereabout Y is variable of clientele decision, X1 is variable of product, X2 is variable of promotion and X3 is variable of attitude. The result show that only attitude had dominate to clientele decision, so, attitude have a big effect on clientele decision to choose sharia banking service. This researches have limited on research period, cause of that suggest for the next researcher have to more period to research this case and expand this research.Keywords : product, promotion, attitude and clientele decision